Protein‐Induced Color Shift of Carotenoids in β‐Crustacyanin1. Issue 39 (21st July 2015) - Gamiz‐Hernandez, Ana P.; Angelova, Iva Neycheva; Send, Robert; Sundholm, Dage; Kaila, Ville R. I.
Abstract β‐Crustacyanin (β‐CR) is a pigment protein responsible for the blue color of lobsters. We show using correlated ab initio calculations how the protein environment tunes the chromophores of β‐CR through electrostatic and steric effects.